The Challenge of Social Workers in Handling Cases of Child Sexual Abuse - Alit Kurniasari (Asian Social Work Journal, 2018)
This article discusses the Social Workers who work in the field of Child Protection, especially those who handle cases of child victims of sexual violence. In many cases, both victims and perpetrators need serious handling in order not to cause further problems. Social workers role are very important in restoring the trauma of children as victims, and addressing children's issues as behaviors including intervening with their families and the environment. During the practice of his profession, it can cause emotional reactions to the child's behavior, such as shock, trust and distrust because the child's sexual experience exceeds his or her age. In addition it can experience burnout, which can affect the practice of his profession. The condition can not be seen as the inability to run the profession, but rather as a challenge for the Social Worker, to improve his professional skills. This paper attempts to provide an alternative solution to minimize the emotional reactions in dealing with cases of Child Sexual Abuse, through a victim-centered approach with the best interests of the child, as a way of resolving conflict in intervention.